Geomorphology of the Tafilalt Basin, South-East Morocco – implications for fluvial–aeolian dynamics and wind regimes. Issue 2 (1st December 2021) - Herzog, Manuel; Henselowsky, Felix; Bubenzer, Olaf
ABSTRACT : The hyper-arid Taflilat Basin, South-East Morocco, is dominated by two ephemeral fluvial networks and several ergs with various dune forms from barchans to mega dunes. Especially the genesis of the star dunes remains an open research question. Therefore, a new multi-sheet geomorphological map describes the surface dynamics in the basin. Identification of major surface features was done with remote sensing data and on-site surveys. The analyses were used to identify all different landscape units. Additionally, aeolian features are emphasized to deduce current wind directions. The identification of two opposite wind fields was possible and a spatial correlation in the fluvial-aeolian system is detected. The border of the opposite wind fields crosses Erg Chebbi. Hence, the star dunes are under the influence of a multimodal wind system. Overall, this new geomorphological map strengthens the understanding of the fluvial-aeolian interaction in the Tafilalt Basin and sets a baseline for ongoing in-depth studies.